2010
DOI: 10.1248/bpb.33.58
|View full text |Cite
|
Sign up to set email alerts
|

R-(-)-.ALPHA.-Methylhistamine, a Histamine H3 Receptor Agonist, Induces Endothelium-Dependent Vasodilation in Rat Mesenteric Resistance Arteries

Abstract: The histamine H 3 receptor, a novel histamine receptor subtype, has been identified in rat brain cortical slices and shown to inhibit histamine release 1,2) in the brain and several peripheral tissues.3,4) Inhibitory presynaptic histamine H 3 receptors have also been found on non-histaminergic nerves including cholinergic, 5) adrenergic 6,7) and non-adrenergic noncholinergic nerves. 8) Characterization of histamine H 3 receptor-mediated responses has been greatly facilitated by the development of selective his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
11
1
1
Order By: Relevance
“…2B). Although we have no clear-cut explanation for this finding, it is tempting to speculate that 31 mg/kg/min immepip could also be interacting with endothelial H 3 receptors producing vasodilatation (Sun et al, 2010); this, in turn, would counteract the sensory-inhibition by immepip. It is noteworthy, within this context, that 31 mg/kg/min immepip is an i. v. continuous infusion (not an i.v.…”
Section: Explanations For the Failure Of Immepip To Produce A Dosedepmentioning
confidence: 81%
See 1 more Smart Citation
“…2B). Although we have no clear-cut explanation for this finding, it is tempting to speculate that 31 mg/kg/min immepip could also be interacting with endothelial H 3 receptors producing vasodilatation (Sun et al, 2010); this, in turn, would counteract the sensory-inhibition by immepip. It is noteworthy, within this context, that 31 mg/kg/min immepip is an i. v. continuous infusion (not an i.v.…”
Section: Explanations For the Failure Of Immepip To Produce A Dosedepmentioning
confidence: 81%
“…This study, however, focussed only on cardiac, rather than perivascular, sensory CGRPergic fibres. More recently, two studies in the isolated rat mesenteric artery have reported that histamine H 3 receptors mediate: (i) endotheliumdependent vasodilatation via the release of nitric oxide, prostaglandin I 2 and/or endothelium-derived hyperpolarizing factors (Sun et al, 2010); and (ii) inhibition of both vascular sympathetic and CGRPergic neurogenic tones in the absence of endothelium (Sun et al, 2011). Consistent with the latter in vitro findings, our study further shows that activation of histamine H 3 receptors results in inhibition of the sensory CGRPergic outflow in the systemic vasculature of pithed rats, and provides additional pharmacological evidence for excluding the role of histamine H 1 , H 2 and H 4 receptors.…”
Section: Generalmentioning
confidence: 99%
“…The vasodilatory response to histamine is predominantly mediated by histamine H 1 receptors located in the endothelium . In addition, some studies have suggested that histamine H 3 receptors are involved in endothelium‐dependent vasodilatory responses . However, the effects of diabetes (as a major risk factor to the cardiovascular system) on histamine‐induced vasodilation is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is possible that histamine receptors, other than those studied here, may be involved in mediating the clinical effects described. Recent animal studies show that H 3 ‐receptors may be important in mediating endothelium dependent vasodilatation . Also, activation of H 1 ‐ and H 4 ‐receptors, together with inhibition of H 3 ‐receptors, are involved in eliciting histamine‐induced itch .…”
Section: Discussionmentioning
confidence: 99%